IMPLEMENTATION OF GAMIFICATION ‘LET'S EXPLORE SCHOLARSHIP’ AS AN INNOVATIVE MEDIUM IN CLASSICAL GUIDANCE SERVICES: ACCESS TO SCHOLARSHIP INFORMATION AT SMAN 5 SERANG CITY - Cristanti, Alfina; Kusuma, Bunga Novelya; Fujiyanti, Annisa; Fadhlih, Ahdanisa; Prabowo, Arga Satrio (Dharmawangsa: International Journal of the Social Sciences, Education and Humanitis, 2025)
This research aims to analyze the effectiveness of the implementation of the gamification "Let's Explore Scholarship" as an innovative media in classical guidance services at SMAN 5 Kota Serang. This research is motivated by students' limitations in accessing scholarship information which is very important to support the continuation of education to a higher level. The gamification media is designed in the form of a "Scholarship Map" which contains interactive quizzes and challenges regarding the types of scholarships, registration procedures, and general requirements that apply. The research method used is descriptive qualitative with data collection techniques through observation, evaluation questionnaires, and student reflection. The research subjects were 30 students of grade X-5 who were selected purposively. The results of the study show that the implementation of the gamification "Let's Explore Scholarship" is able to increase students' enthusiasm, motivation, and critical thinking skills in exploring scholarship information. In addition, students also gain a better understanding of scholarship pathways and strategies for continuing their education to higher education. The implementation of this gamification creates a more enjoyable, interactive, and participatory learning atmosphere in classical guidance services. Thus, the gamification of “Let’s Explore Scholarship” can be an effective alternative strategy to equip students with knowledge, motivation, and readiness to achieve a brighter future through access to scholarship information.